2014
DOI: 10.1002/2013ja019086
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric response to the ultrafast Kelvin wave in the MLT region

Abstract: The modulation of the ultrafast Kelvin wave (UFKW) on the equatorial ionosphere is investigated, using satellite neutral wind and temperature observations in the mesosphere/lower thermosphere (MLT) and ground-based global maps of total electron content (TEC) observations. The UFKW signatures are identified in the least squares fitting spectra for MLT zonal wind, temperature, TEC, and Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) electron density profiles, providing strong evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
70
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(80 citation statements)
references
References 41 publications
10
70
0
Order By: Relevance
“…As shown in numerous previous studies, the four‐peak structure in the ionosphere results from the ionosphere and atmosphere couplings through DE3 [ Immel et al , ; Hagan et al , ; Oberheide et al , ; Pancheva et al , ; Pedatella et al , ]. The UFKW‐related signatures have also been clearly identified in the ionosphere [ Chang et al , ; Liu et al , ; Gu et al , ]. Given the similarity of the latitudinal structure of the zonal wind components among these waves, the 6 day wave in the equatorial lower thermosphere would modulate the ionosphere through E region wind dynamo as the DE3 and UFKW.…”
Section: Discussion and Summarymentioning
confidence: 68%
See 3 more Smart Citations
“…As shown in numerous previous studies, the four‐peak structure in the ionosphere results from the ionosphere and atmosphere couplings through DE3 [ Immel et al , ; Hagan et al , ; Oberheide et al , ; Pancheva et al , ; Pedatella et al , ]. The UFKW‐related signatures have also been clearly identified in the ionosphere [ Chang et al , ; Liu et al , ; Gu et al , ]. Given the similarity of the latitudinal structure of the zonal wind components among these waves, the 6 day wave in the equatorial lower thermosphere would modulate the ionosphere through E region wind dynamo as the DE3 and UFKW.…”
Section: Discussion and Summarymentioning
confidence: 68%
“…In addition, the ultra fast Kelvin wave (UFKW), which is capable of propagating directly from the lower atmosphere to the lower thermosphere due to its long vertical wavelength [ Forbes , ; Chang et al , ; Gu et al , ], has also been found to induce similar wave signals in the ionosphere through electro dynamo processes [ Forbes , ; Liu et al , ]. The global distributions of the UFKW signals in TEC also agree well with the equatorial fountain effect [ Chang et al , ; Liu et al , ; Gu et al , ].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Even at geomagnetic and solar quiet conditions, the equatorial ionosphere has been found to exhibit a large day‐to‐day variability [e.g., Laštovička , ]. Much of this variability has been attributed to the forcing by atmospheric planetary‐scale waves with periods of 2–16 days [e.g., Forbes , ; Pancheva et al ., ; Takahashi et al ., ; Liu et al ., ; Chang et al ., ; Liu et al ., ; Gu et al ., ]. These waves originate in the lower atmosphere, and with increasing altitude their amplitudes increase while the background densities decrease.…”
Section: Introductionmentioning
confidence: 99%